Practicality of a Cognitive Conflict-Based Physics Website Integrated with AR-STEM to Promote Critical Thinking and Misconception Remediation in Dynamic Fluid - Irene Dwi Cahyani; Fatni Mufit; Hidayati Hidayati; Yeka Hendriyani; Zahra Fathanah (Universitas Negeri Padang in collaboration with Association of Mathematics and Natural Sciences Institution for Education of Teaching Staff Indonesia (AMLI), 2026)
Ideally, physics learninghould be supported by innovative instructional materials that can develop students' critical thinking skills and help them overcome misconceptions. One potential solution is a cognitive conflict-based physics website integrated with Augmented Reality (AR) and STEM. This study aimed to analyze the practicality of a cognitive conflict-based physics website integrated with AR and STEM as a digital learning resource. The study was part of a research and development project employing the Plomp model, focusing on the one-to-one evaluation and small group evaluation stages. The participants consisted of 12 senior high school students in Phase E at SMA Negeri 6 Padang. Data were collected using a practicality questionnaire covering four aspects: ease of use, attractiveness, efficiency, and usefulness. The data were analyzed using percentage analysis. The results showed that the website achieved an average practicality score of 88% in the one-to-one evaluation stage and 86% in the small group evaluation stage, both categorized as highly practical. Furthermore, all practicality aspects were rated as highly practical during the small group evaluation. These findings indicate that the website is easy to use, engaging, efficient, and beneficial for physics learning. Therefore, the cognitive conflict-based physics website integrated with AR and STEM is suitable for use as a digital learning resource and is ready to proceed to the effectiveness testing stage to investigate its impact on students' critical thinking skills and the remediation of misconceptions.